Georg Martin Wunderlich papers - Wunderlich, Georg Martin, 1883-1951.
Correspondence, diaries, manuscripts of unpublished studies, legal writings, notebooks, biographical material, military documents, academic records, financial records, clippings, printed matter, photographs, memorabilia, and other papers relating primarily to Wunderlich's career in law in Germany and the United States. Documents his legal education in Germany; activities on behalf of clients in West Africa and elsewhere; services to the German Imperial Government during World War I as military judge in Belgium and Turkey; postwar rise in Berlin as a writer and authority on international law; his forced emigration as a Jew in 1936; adjustment to the Anglo-American legal system; teaching duties at the University of Pennsylvania; and services during World War II as special counsel to the U.S. State Dept. Includes correspondence with and concerning the American Society of International Law and the International Law Association.
International lawyer, professor of law, and consultant to the U.S. Dept of State.
Collection material in German and English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: United States. -- Department of State; American Society of International Law; American Society of International Law -- Correspondence; International Law Association; International Law Association -- Correspondence; University of Pennsylvania. -- Law School; International law; Judges -- Belgium; Judges -- Turkey; Law -- Methodology; Law -- Philosophy; Law -- Study and teaching -- Germany; Law -- Study and teaching -- United States; Law -- Germany; Law -- United States; Practice of law -- Africa, West; Universities and colleges -- Pennsylvania; World War, 1914-1918 -- Germany; World War, 1939-1945.; Germany -- Emigration and immigration; United States -- Emigration and immigration; Educators; Lawyers